Swim Speed Tests as a Method for Differentiating the Profiles of Young Swimmers - Klara Šiljeg; Joško Sindik; Goran Leko (Montenegrin Sports Academy, 2017)
Swimming tests are used in every training cycle and seasons with purpose of estimating swimming performance and evaluate certain training types. The focus of this study is an attempt to distinguish between the potential short-distance and longer-distance swimmers, as well as the swimmers who could have desirable profiles for particular swimming styles. For this purpose, several aims are given: () to determine the latent dimensions of the performances in swimming tests, conducted on various distances and performed using different swimming styles; 2) to determine the correlations between speeds on various distances using different swimming styles; 3) to determine the differences in various distance speeds at the same swimmers ; 4) to determine the profiles of swimmers, based on the various distance speeds (4). Male swimmers (N=68), aged 14 to 16 from five Zagreb clubs were tested. Four swimming tests were used to measure speed (25-m freestyle, backstroke, breaststroke, butterfly), five swimming tests measured speed endurance (50-m freestyle, 100-m freestyle, backstroke, breaststroke, butterfly), while only one test measured endurance (800-m freestyle). The results revealed two interpretable and highly reliable latent dimensions of swimming tests. Factor analysis of the scores in swimming tests differentiated the variables of swimming tests that describe breaststrokes and other strokes. Most of the scores in the swimming tests are positively correlated (in range 0.25-0.85), while no differences in various distance speeds among the same swimmers are found. The results indicate the importance of using swimming tests, especially in breaststrokes styles, because of their specific motor structure.